Prevalence of psychological distress and source of stressors among undergraduate science students in Malaysia - Al-Ani, Ali Sabri Radeef; Faisal, Ghasak Ghazi (2014)
Background: Students in higher education are subjected to different levels of stressors during various stages of their study. Stress during education can lead to mental distress and have negative impact on cognitive functioning and learning and may affect their mental and physical health as well. Therefore, this study aimed to determine the prevalence of psychological distress among undergraduate students of Kulliyyah of Science and to identify the source of stressors and their relationship with psychological distress. Methods: A cross sectional, questionnaire-based study was conducted among 196 undergraduate science students from Kulliyyah of Science, International Islamic University Malaysia (IIUM) during the period from March 2013 to June, 2013. The psychological distress was assessed using the 12-item General Health Questionnaire (GHQ-12), which is the short version developed by David Goldberg and Paul Williams. The students were given a list of the most possible source of stressors. In this list, the stressors were chosen depending on previous studies, then the association of the top ten stressors with psychological distress were assessed. Results: The prevalence of psychological distress among Science students was found to be 38.8% and the rate was significantly higher among female than male students while there was no significant association with age, household income, year of study and family support. The top ten stressors chosen by the students were academic and personal related factors and five factors were significantly associated with psychological distress namely, feeling of incompetence, lack of motivation to learn, amount of assigned class work, academic overload and study pressure and obligation.